2012
DOI: 10.1039/c2fd20022h
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes of deposited casein micelles induced by membrane filtration

Abstract: Casein micelles undergo shape changes when subjected to frontal filtration forces. Grazing incidence small angle X-ray scattering (GISAXS) and atomic force microscopy (AFM) allow a quantification of such structural changes on filtration cakes deposited on smooth silicon micro-sieves. A trans-membrane pressure of deltap = 400 mbar across the micro-sieve leads to an immediate film formation after deposition of casein solution. We observe significant changes in the GISAXS pattern depending on how many layers are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…They found that CMs arrange in a hexagonal lattice when forming deposit layers on membranes. In addition, experimental data from AFM and mGISAXS experiments indicate that CMs are subjected to an ellipsoidal shape change when CMs are exposed to elongational flow of the filtrate through the CM deposit towards the membrane pores [21]. This result is in good agreement with the studies on CM deposit compressibility [22] or the behavior of CMs under osmotic stress [13,14].…”
Section: Introductionsupporting
confidence: 57%
“…They found that CMs arrange in a hexagonal lattice when forming deposit layers on membranes. In addition, experimental data from AFM and mGISAXS experiments indicate that CMs are subjected to an ellipsoidal shape change when CMs are exposed to elongational flow of the filtrate through the CM deposit towards the membrane pores [21]. This result is in good agreement with the studies on CM deposit compressibility [22] or the behavior of CMs under osmotic stress [13,14].…”
Section: Introductionsupporting
confidence: 57%
“…Grazing-incidence small-angle X-ray scattering (GISAXS) allows, for instance, for investigations on samples prepared on a solid support and hence for a direct comparison with those obtained from AFM measurements. GISAXS has been used to investigate changes of the natural conformation and size distribution of CM in films (Gebhardt et al, 2010 but more recently also in deposits on porous micro-sieves (Gebhardt et al, 2012). In all three studies the sizes estimated with GISAXS were in good accordance with those obtained by AFM.…”
Section: Introductionmentioning
confidence: 56%
“…8 however indicate that the microgel particles are quantitatively retained by the 3 kDa MWCO membrane. Some recent studies have shown that protein micelle undergo deformation during filtration [31,32], and therefore have attributes similar to microgel filtration.…”
Section: Resultsmentioning
confidence: 98%